MIXED METHOD: STUDENTS’ ABILITY IN APPLYING POSSESSIVE PRONOUN IN WRITING SENTENCES AT THE 1ST SEMESTER FKIP UNILAK PEKANBARU - Syahdan Syahdan (Lectura : Jurnal Pendidikan, 2016)
As the students of English Department, the students should be able in doing grammarwell, in this case Possessive Pronoun. The purpose of this research was to find out the students’ability in applying Possessive Pronoun and their common problem in applying PossessivePronoun in writing sentences at 1st semester FKIP UNILAK Pekanbaru. The type of the researchwas mixed method in type of explanatory design. The number of population was 105 students, theresearcher took 53 students as sample of the 1st semester FKIP UNILAK Pekanbaru selected bysimple random sampling. In collecting the data the researcher used two instrument, test andinterview. The form of test was essay test. The interview is held to support the data. In analyzingthe data, the researcher used SPSS in descriptive statistics. The result of the analysis showedthat the average score of 1st semester student in applying Possessive Pronoun was 52.98.Meanwhile for the median is 48, the mode is 20. The score of Standard Deviation is 27.93,Variance is 780.25, and Range is 84. According to the Z-Score, it can be seen that 41.5%students’ ability was higher than average and 58.5% students ability was below the average. Itcan be seen that students’ ability in applying Possessive Pronoun was low. For the commonproblem, based on the test, students still mixed up between Possessive Pronoun and PossessiveAdjectives. Students used wrong pattern in using Possessive Pronoun, in which they still useSubject or Object Pronoun. Based on interview, students did not understand clearly aboutPossessive Pronoun, also they have difficulties in learning Possessive Pronoun, for the reason ofabsence of review the lesson. In conclusion, students’ ability in applying Possessive Pronouncorresponds with their common problem.